If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6q=5q+6
We move all terms to the left:
6q-(5q+6)=0
We get rid of parentheses
6q-5q-6=0
We add all the numbers together, and all the variables
q-6=0
We move all terms containing q to the left, all other terms to the right
q=6
| `x=-10 | | 2x-6+2-(-x)=4x-3-(-1) | | 5+4j+8j=9j-10 | | `x=-10` | | -2x+14=-4x+22 | | 12x+x=67 | | -4n-2=-4-6n | | 4(-x-3)=-6x+8 | | -5(-4y+6)-2y=6(y-4)-4 | | 6c-10=10c+10 | | 433.11=220+1.01x | | 189=−1+10m | | x-6/9=22 | | 5p+7=-3+7p-2 | | (5x-60)=15+2x+3 | | 6x-10+26+4x=180 | | -11f-23=8 | | 40=35x=80+25x | | 6x+2^3=2x-12 | | H+9/5=(h-1)/3 | | x-9,56=1.5 | | 5(x-7)+x=6(x-4) | | 7n=18-(-2n) | | –2n+4=–3n | | 3x+7–x+12=45 | | -8+2n=-n+4 | | -15h=-420 | | -4=-12-s/8 | | (x+5)^2(2x-3)^2=46 | | -7+2d=-5d | | 18=-5b17 | | (W+6)(w-5)=0 |